Pembaharuan Pendidikan Islam Studi Pemikiran Fazlur Rahman Tentang Konsep Pendidikan Tinggi Islam - Hujair AH. Sanaky (EL-TARBAWI, 2002)
This article traces that the essence of Islamic education, according Fazlur Rahman, does not only refer to the material equipments for instance the text books, that were taught or external structure of education but it teas also according to Rahman that aimed of Islamic Education was "Islamic Intellectualism The higher education of Islamic should he based on the method of interpretation of Quran, and it becomes the basic of Islamic Intellectualism Construction. Rahman offered the concept of the higher Islamic of Education Starting from the comprehensive understanding Qitran because Quran constituted the guidance and inspired young generation of Islamic of higher Islamic of Education denoted open curriculum for social sciences and philosophical approach.Key Word : Islamic Intellectualism, the Higher Islamic of Education